2018
DOI: 10.1111/jam.13729
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitory effect of Spirogyra spp. algal extracts against herpes simplex virus type 1 and 2 infection

Abstract: Anti-HSV activity of extract of freshwater green macroalga Spirogyra spp. in Thailand was demonstrated. Therefore, anti-HSV product containing the Spirogyra spp. extract should be developed for treatment of HSV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
(54 reference statements)
0
8
0
1
Order By: Relevance
“…C10 and C11 reduced significantly the areas of formed viral plaques when compared to viral controls, and these results could be a consequence of the inhibition of viral release. Several studies have demonstrated the anti-herpes activity of natural products, some of which interfere with early steps [41,42,[56][57][58][59][60][61][62][63][64], while a few affect the last steps of HSV replication [65][66][67][68], as was demonstrated for C10 and C11. For this reason, both cardenolides could be used in combination with other natural products to ensure that different stages of HSV replication would be inhibited, for example with transresveratrol, for which significant anti-HSV activity has also been described [69].…”
Section: Discussionmentioning
confidence: 82%
“…C10 and C11 reduced significantly the areas of formed viral plaques when compared to viral controls, and these results could be a consequence of the inhibition of viral release. Several studies have demonstrated the anti-herpes activity of natural products, some of which interfere with early steps [41,42,[56][57][58][59][60][61][62][63][64], while a few affect the last steps of HSV replication [65][66][67][68], as was demonstrated for C10 and C11. For this reason, both cardenolides could be used in combination with other natural products to ensure that different stages of HSV replication would be inhibited, for example with transresveratrol, for which significant anti-HSV activity has also been described [69].…”
Section: Discussionmentioning
confidence: 82%
“…had highly significant inhibition of the viral infection on HSV-1 and HSV-2, respectively, when treated during the viral infection phase of Vero cells. The alkaloids, essential oils and terpenoids present in the freshwater macroalgae were regarded as the main active compounds responsible for anti-viral activity (Deethae et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Deethae et al 158 created aqueous, ethanolic, and methanolic extracts from the freshwater green algae Spirogyra and investigated antiviral activity against HSV-1 (strain F) and HSV-2 (strain G). Firstly, effects were when extracts were added to cells before, during, and after viral attachment.…”
Section: Asiamentioning
confidence: 99%